Analisis Cakupan Pemeriksaan Kehamilan di Wilayah Kerja Puskesmas Wolio Kota Baubau - Wahyuddin, Wahyuddin; Darmawan, Agus; Meilani, Nima; taswin, Taswin (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2021)
The visiting scope for pregnancy woman can be percentage with using indicator performance K1 and K4. Wolio health center have pregnancy check up scope in 2017 wes low, compane with pregnancy check up scope in 2016 was high. The purpose of this research is to know the related factor with pregnancy check up scope in working area wolio association public health of Baubau City. The kind of research that using is quantitative cross sectional approachment. With 122 population of people that do pregnancy check up in working area of wolio health center of baubau town in 2018. The sample in this research taken by total sampling method. The data collection by primer data with quisioner and do direct observation and secondary data. Tabulation of data analysis with SPSS with chi-square (α=0,05) test. The result of research show that there are related between quality of pregnancy check up (p value = 0,002 < 0,05), distance between home and health fasilitation (p value = 0,011 < 0,05), the support of family (p value = 0,005 < 0,05) pregnancy check up scope in wolio health center of Baubau town. The conclusion of this research tell that the quality of pregnancy check up, the distance between home to health facilitation and family support have close relation ship with pregnancy check up scope. The sugestion to health center side is to be desirable that increase the approachment and cooperation with the society.